Faktor pembentuk brand loyalty: peran self concept connection, brand love, brand trust dan brand image (telaah pada merek h&m di kota dki jakarta) - Andriani, Meta; dwbunga, Frisca (Universitas Muhammadiyah Surakarta, 2017)
Brand loyalty or customer loyalty is an important concept for many companies that can bring many benefits to companies, such as repeat purchases and brand recommendations to others, who then can reduce marketing costs. Trust in the brand is important and is a major factor in the development of brand loyalty. Along with the development of industry, entertainment, information and technology, style of fashion becomes a medium to demonstrate the existence of a person in the community. By following certain fashion, people can show their true identity. The purpose of this study was to determine the role of the Self Concept Connection, Brand Love, Brand Trust and Brand Image on the increase Brand Loyalty.The focus of this study object is H&M brand in Jakarta region. The data used in this study were gathered by spreading the questionnaires to users who have purchased the H&M brand is more than one time. This study used convinience sampling as a sampling technique and obtained 158 respondend and this data processed into this study result. This study uses SEM analyze to test the data.